A production process of high-friction non-slip composite floor mat substrate

CN122896448APending Publication Date: 2026-10-13SUZHOU GONGYEYUAN DISTRICTHEXIANG TEXTILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611211829.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]3.TPE/TPR淋膜压纹防滑结构:仅依靠宏观纹路增加摩擦力,摩擦提升幅度低;仅能单层成型,无法实现多层功能复合,缓冲、支撑、防滑性能无法兼顾

Benefits of technology

1.通过向SEBS树脂中引入纳米二氧化硅并经硅烷偶联剂改性,显著提高了SEBS防滑母粒的摩擦系数和耐磨性。纳米二氧化硅作为刚性粒子,在摩擦过程中能够起到“微凸起”作用,增大接触面的实际接触面积和犁削阻力;同时,硅烷偶联剂的引入使纳米二氧化硅与SEBS基体之间形成化学键合,避免了无机粒子在磨损过程中的脱落,保证了防滑性能的持久性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122896448A_ABST
    Figure CN122896448A_ABST
Patent Text Reader

Abstract

The application relates to a production process of a high-friction anti-skid composite ground mat substrate, and comprises the following steps: step one: preparing a modified SEBS anti-skid master batch, wherein SEBS resin 100 parts, naphthenic oil 30-50 parts, nano-silicon dioxide 8-15 parts, silane coupling agent 2-5 parts and antioxidant 0.5-1.5 parts are put into a high-speed mixer and mixed at a temperature of 80-120 DEG C for 15-30 minutes, then the mixture is melt-extruded and granulated through a double-screw extruder to obtain the modified SEBS anti-skid master batch; the friction coefficient and wear resistance of the SEBS anti-skid master batch are significantly improved by introducing nano-silicon dioxide into the SEBS resin and modifying the nano-silicon dioxide through a silane coupling agent. The nano-silicon dioxide acts as a rigid particle and can play a "micro-protrusion" role in the friction process, so that the actual contact area of the contact surface and the plowing resistance are increased; meanwhile, the introduction of the silane coupling agent forms a chemical bond between the nano-silicon dioxide and the SEBS matrix, so that the falling of the inorganic particles in the wear process is avoided, and the durability of the anti-skid performance is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of floor mat material technology, and relates to a production process for a high-friction anti-slip composite floor mat substrate. Background Technology

[0002] Anti-slip mats are widely used in slippery environments such as home bathrooms, hotel corridors, gyms, hospital wards, and swimming pool areas. The core performance indicators of the material are the static / dynamic coefficients of friction in dry and wet conditions, interlayer bond strength, and wear resistance and service life. Currently, the mainstream anti-slip mat manufacturing methods on the market have significant shortcomings: 1. EVA foam base layer + surface coating with anti-slip oil film: The anti-slip coating is only physically attached and will fall off after long-term trampling and wear; when it comes into contact with water, the liquid forms a lubricating film, the wet friction coefficient decreases significantly, and the difference in dry and wet anti-slip performance is huge.

[0003] 2. SEBS anti-slip layer glued to PET substrate: Pure SEBS itself has limited friction enhancement and relies on adhesive bonding, which has no molecular bonding force. After long-term bending and alternating hot and cold temperatures, it is prone to delamination and peeling.

[0004] 3. TPE / TPR coated embossed anti-slip structure: It only relies on macroscopic texture to increase friction, and the friction increase is low; it can only be molded in a single layer and cannot achieve multi-layer functional composite, so it cannot take into account buffering, support and anti-slip performance. Summary of the Invention

[0005] The purpose of this invention is to provide a production process for a high-friction, anti-slip composite floor mat substrate, which can solve the problems mentioned in the background art.

[0006] According to the technical solution provided by this invention: a production process for a high-friction anti-slip composite floor mat substrate includes the following steps: Step 1: Preparation of modified SEBS anti-slip masterbatch - By weight, 100 parts of SEBS resin, 30-50 parts of naphthenic oil, 8-15 parts of nano silica, 2-5 parts of silane coupling agent, and 0.5-1.5 parts of antioxidant are added into a high-speed mixer and mixed at 80-120℃ for 15-30 minutes. The mixture is then melt-extruded and granulated using a twin-screw extruder to obtain the modified SEBS anti-slip masterbatch. Step 2: Preparation of Gradient Foamed Substrate Layer – Mix 80-100 parts of EVA resin, 20-40 parts of the modified SEBS anti-slip masterbatch, 3-8 parts of foaming agent, 0.5-2 parts of crosslinking agent, 2-5 parts of zinc oxide, and 0.5-1.5 parts of stearic acid evenly. Then, mix the mixture in an internal mixer at 100-130℃ for 8-15 minutes, and then pass it through a two-roll mill 3-5 times. After sheeting, send it to a flat vulcanizing machine and foam and crosslink at 160-190℃ and 8-15MPa for 8-20 minutes to obtain a gradient foamed substrate layer. The gradient foamed substrate layer has a foam density gradient along the thickness direction, with a foam density of 0.25-0.35 g / cm³ near the upper surface and a foam density of 0.45-0.60 g / cm³ near the lower surface. Step 3: Preparation of the friction functional layer—80-100 parts of thermoplastic polyurethane resin, 30-50 parts of the modified SEBS anti-slip masterbatch, 5-15 parts of polytetrafluoroethylene micro powder, 3-10 parts of silicon carbide micro powder, and 1-3 parts of dispersant are mixed, melt-blended and extruded into granules using a twin-screw extruder, and then cast into a film at 180-220℃ using a casting machine, with a film thickness of 0.2-0.8 mm, to obtain the friction functional layer; Step 4: Plasma activation treatment—The upper surface of the gradient foamed substrate layer and the lower surface of the friction functional layer are subjected to low-temperature plasma treatment. The treatment gas is a mixture of argon and oxygen, the treatment power is 200-500W, and the treatment time is 30-120 seconds. Step 5: Hot-press lamination - The gradient foamed substrate layer after plasma activation treatment is stacked with the triboelectric functional layer. The layer is hot-pressed for 3-10 minutes at a temperature of 150-200℃ and a pressure of 3-10MPa to form an interpenetrating network structure between the triboelectric functional layer and the gradient foamed substrate layer. Step Six: Surface Microstructure Imprinting – On the surface of the friction functional layer of the substrate after hot pressing and lamination, an imprinting roller with a micro-protrusion array is used to perform hot pressing to form a biomimetic micro-protrusion array structure on the surface of the friction functional layer. Step 7: Gradient cooling and shaping – The imprinted composite floor mat substrate is sequentially cooled through three temperature zones. The first temperature zone is 80-100℃, the second temperature zone is 40-60℃, and the third temperature zone is 15-25℃. The dwell time in each temperature zone is 2-5 minutes, resulting in the finished high-friction anti-slip composite floor mat substrate.

[0007] Preferably, the SEBS resin in step one is a mixture of linear SEBS and star-shaped SEBS, with a weight ratio of linear SEBS to star-shaped SEBS of 1:1 to 3:1.

[0008] Preferably, the average particle size of the nano-silica in step one is 20-80 nm, and the nano-silica is subjected to segmented coupling treatment. Pre-coating stage: 40%–60% of the total weight of silane coupling agent is mixed with nano-silica at a weight ratio of 10:1–5:1 and stirred at 100–120°C for 1–3 hours to obtain pre-coated nano-silica with surface grafted coupling agent and remaining active hydroxyl groups. Secondary bonding stage: The remaining 40%–60% of the silane coupling agent is added together with SEBS resin, naphthenic oil and the above-mentioned pre-coated nano silica in the high-speed mixer described in step one. Under the high temperature and high shear environment of melt blending in a twin-screw extruder, the remaining coupling agent reacts chemically with the remaining hydroxyl groups on the surface of nano silica and the polar groups generated on the SEBS molecular chain due to thermo-oxidation, forming a three-dimensional chemical bonding network of "nano silica—coupling agent—SEBS".

[0009] Preferably, the silane coupling agent in step one is γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane.

[0010] Preferably, the density gradient change rate of the gradient foamed substrate layer is 0.015−0.035g / cm3 / mm. This density gradient change rate is achieved by adjusting the temperature difference between the upper and lower heating plates of the flat vulcanizing machine. The temperature difference between the upper and lower heating plates is 5−15℃. When the substrate thickness decreases, the density difference caused by excessive heat transfer in the thin plate is suppressed by reducing the temperature difference between the upper and lower heating plates or simultaneously reducing the absolute temperature of the upper heating plate.

[0011] Preferably, the average particle size of the silicon carbide micro powder in step three is 5-30 μm, and the average particle size of the polytetrafluoroethylene micro powder is 1-10 μm.

[0012] Preferably, the volume ratio of the argon and oxygen mixture in step four is 3:1-5:1, and the processing pressure is 20-80 Pa.

[0013] Preferably, the thickness of the interpenetrating network structure described in step five is 50-200 μm.

[0014] Preferably, in the biomimetic micro-protrusion array structure described in step six, the height of the micro-protrusions is 50-300μm, the diameter is 30-80μm, the areal density is 100-500 protrusions / mm², and the top of the micro-protrusions is mushroom-shaped or dome-shaped.

[0015] Preferably, the hot pressing composite in step five is carried out under vacuum conditions, with a vacuum degree of 0.01-0.1 MPa.

[0016] The present invention provides a manufacturing process for a high-friction, anti-slip composite floor mat substrate, which has the following advantages: 1. By introducing nano-silica into SEBS resin and modifying it with a silane coupling agent, the coefficient of friction and wear resistance of SEBS anti-slip masterbatch were significantly improved. As rigid particles, nano-silica acts as "micro-protrusions" during friction, increasing the actual contact area and ploughing resistance. Simultaneously, the introduction of the silane coupling agent forms a chemical bond between the nano-silica and the SEBS matrix, preventing the inorganic particles from detaching during wear and ensuring the durability of the anti-slip performance.

[0017] 2. The substrate layer prepared using gradient foaming technology has a density gradient distribution along the thickness direction—the upper surface has a lower density (0.25-0.35 g / cm³) to provide good cushioning and a soft touch, while the lower surface has a higher density (0.45-0.60 g / cm³) to provide sufficient structural support and dimensional stability. This gradient structure allows the substrate to deform step by step under pressure, ensuring both comfort when stepping on it and preventing anti-slip failure caused by the overall collapse of the substrate.

[0018] 3. By combining low-temperature plasma activation treatment with hot-pressing, an interpenetrating network structure is formed between the triboelectric functional layer and the gradient foamed substrate layer. The plasma treatment introduces active groups (such as hydroxyl, carboxyl, and amino groups) on the surfaces of the two materials, reducing the interfacial energy and improving surface activity. Under hot-pressing conditions, some TPU molecular chains and modified SEBS molecular chains in the triboelectric functional layer diffuse into the surface pores of the substrate layer, entangle with EVA and SEBS molecular chains, and form an interpenetrating transition zone with a thickness of 50-200 μm. This interpenetrating network structure fundamentally solves the problems of weak interlayer bonding and easy delamination in traditional adhesive bonding methods, enabling the triboelectric functional layer and the substrate layer to form an "integrated" structure rather than an "adhesive" structure.

[0019] 4. A biomimetic micro-protrusion array structure was prepared on the surface of the friction functional layer using hot embossing technology, mimicking the microscopic morphology of gecko paw bristles or tree frog foot pads. Unlike traditional anti-slip textures that rely solely on macroscopic bumps and depressions to increase friction, the biomimetic micro-protrusion array of this invention has multiple anti-slip mechanisms: multiple independent contact points are formed between the micro-protrusions and the contact surface, increasing the actual contact area; the mushroom-shaped or dome-shaped tops of the micro-protrusions undergo elastic deformation under pressure, generating a "suction cup effect" to enhance adsorption force; the microgrooves between the micro-protrusions provide drainage channels for liquids (such as water and oil), reducing the lubricating effect of the liquid film on friction; the synergistic effect of these three factors gives the substrate excellent anti-slip performance under both dry and wet conditions. Attached Figure Description

[0020] Figure 1 This is a process step diagram of the present invention. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] In the description of this invention, it should be understood that the terms "upper", "lower", "front", "rear", "left", "right", "top", "bottom", "inner", "outer", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.

[0023] like Figure 1 As shown, a manufacturing process for a high-friction, anti-slip composite floor mat substrate includes the following steps: Step 1: By weight, 60 parts of linear SEBS resin, 40 parts of star-shaped SEBS resin, 40 parts of naphthenic oil, 12 parts of nano-silica (average particle size 50nm) pretreated with KH-550, and 10101 parts of antioxidant are added into a high-speed mixer and mixed at 100°C for 20 minutes. The mixture is then melt-extruded and granulated at 190°C using a twin-screw extruder to obtain modified SEBS anti-slip masterbatch.

[0024] The average particle size of the nano-silica in step one is 20-80 nm, and the nano-silica is subjected to segmented coupling treatment. Pre-coating stage: Silane coupling agent accounting for 40%-60% of the total weight of silane coupling agent is mixed with nano silica at a weight ratio of 10:1-5:1 and stirred at 100-120℃ for 1-3 hours to obtain pre-coated nano silica with surface grafted coupling agent and remaining active hydroxyl groups. Secondary bonding stage: The remaining 40%–60% of the silane coupling agent is added together with SEBS resin, naphthenic oil and the above-mentioned pre-coated nano silica in the high-speed mixer described in step one. Under the high temperature and high shear environment of melt blending in a twin-screw extruder, the remaining coupling agent reacts chemically with the remaining hydroxyl groups on the surface of nano silica and the polar groups generated on the SEBS molecular chain due to the action of heat and oxygen, forming a three-dimensional chemical bonding network of "nano silica-coupling agent-SEBS". In the pretreatment stage, only a portion of the coupling agent is used to coat the surface of nano-silica. The purpose is to prevent nanoparticle aggregation and initially introduce organic functional groups, rather than completely occupying all surface active sites. The remaining coupling agent is added during the masterbatch preparation stage. Utilizing the high-temperature shear force of the twin-screw extruder, it can continue to dehydrate and condense with residual hydroxyl groups on the SiO2 surface, and also undergo grafting reactions with double bonds or oxidative active sites on the SEBS molecular chain. Simultaneously, the twin-screw extruder is equipped with a vacuum exhaust section (vacuum degree 0.02–0.06 MPa), which can immediately remove the very small amount of unreacted free coupling agent and its potential self-condensed polysiloxane oligomers from the system. This ensures that no free small molecules remain in the final masterbatch, fundamentally eliminating the technical risk of free coupling agent weakening interfacial bonding. This effectively achieves a significant improvement in the strong chemical bond between inorganic particles and the SEBS matrix, as well as enhanced anti-slip durability.

[0025] Step 2: Mix 90 parts of EVA resin (VA content 18%), 30 parts of modified SEBS anti-slip masterbatch, 5 parts of AC foaming agent, 1 part of DCP crosslinking agent, 3 parts of zinc oxide, and 1 part of stearic acid evenly. Then, mix the mixture in an internal mixer at 120°C for 12 minutes. Next, pass the mixture through a two-roll mill four times. After sheeting, send the sheet to a flat vulcanizing machine. The substrate layer (8 mm thick) was foamed and crosslinked at 180℃ and 12 MPa for 15 minutes to obtain a gradient foamed substrate layer. The density of the upper surface was 0.30 g / cm3, the density of the lower surface was 0.52 g / cm3, and the density gradient change rate was 0.0275 g / cm3 / mm.

[0026] For thin sheet applications (e.g., 4mm thick): the temperature of the upper heating plate of the flat vulcanizing machine is set to 170℃, and the temperature of the lower heating plate is set to 178℃ (temperature difference 8℃). The foaming time is shortened to 10 minutes. Under these conditions, a 4mm thick substrate layer is obtained with an upper surface density of 0.34g / cm³ and a lower surface density of 0.45g / cm³, resulting in a density difference of 0.11g / cm³. This maintains a precise gradient change rate of 0.0275g / cm³ / mm. Therefore, those skilled in the art can flexibly control the density difference for different thicknesses simply by adjusting the temperature difference between the upper and lower molds according to the thickness adaptability, without any technical obstacles.

[0027] Step 3: Mix 90 parts of TPU resin (polyester type, hardness 85A), 40 parts of modified SEBS anti-slip masterbatch, 10 parts of PTFE micro powder (average particle size 5μm), 6 parts of silicon carbide micro powder (average particle size 15μm), and 2 parts of dispersant (stearamide). Then, melt-blend and granulate the mixture using a twin-screw extruder at 200℃, and then cast it into a film with a thickness of 0.5mm using a casting machine at 200℃ to obtain the friction functional layer.

[0028] Step 4: Perform low-temperature plasma treatment on the upper surface of the gradient foamed substrate layer and the lower surface of the friction functional layer. The treatment gas is a mixture of argon and oxygen (volume ratio 4:1), the treatment power is 350W, the treatment time is 60 seconds, and the treatment pressure is 50Pa.

[0029] Step 5: The gradient foamed substrate layer after plasma activation treatment is laminated with the triboelectric functional layer and hot-pressed for 6 minutes under vacuum of 0.05 MPa, temperature of 180°C and pressure of 6 MPa.

[0030] Step Six: On the surface of the friction functional layer of the substrate after hot pressing and lamination, hot pressing is performed using an imprinting roller with a mold pattern of micro-protrusions resembling gecko paw bristles. The imprinting temperature is 140℃, the imprinting pressure is 4MPa, and the imprinting speed is 3m / min, forming a mushroom-shaped array of micro-protrusions with a height of 150μm, a diameter of 80μm, and a surface density of 300 protrusions / mm² on the surface of the friction functional layer.

[0031] Step 7: Pass the imprinted composite floor mat substrate through three temperature zones in sequence: the first temperature zone 90℃ (3 minutes), the second temperature zone 50℃ (3 minutes), and the third temperature zone 20℃ (3 minutes), with a cooling rate of 10℃ / min, to obtain the finished high-friction anti-slip composite floor mat substrate.

[0032] The substrate obtained in this embodiment was subjected to performance tests: the dry static friction coefficient was 1.35, the wet static friction coefficient was 0.95, the dry dynamic friction coefficient was 0.85, and the wet dynamic friction coefficient was 0.65; the interlayer peel strength was 8.5 N / cm; and the friction coefficient retention rate was ≥92% after 10,000 abrasion resistance tests. Example 2

[0033] The difference from Example 1 is as follows: In step one, the SEBS resin is all linear SEBS (100 parts), naphthenic oil is 35 parts, nano silica (average particle size 30nm) is 15 parts, and KH-560 coupling agent is 4 parts; In step two, EVA resin (VA content 22%) is 85 parts, modified SEBS anti-slip masterbatch is 35 parts, OBSH foaming agent is 6 parts, TAIC crosslinking agent is 1.5 parts, the foaming temperature is 175℃, and the foaming time is 18 minutes; In step six, the imprinting temperature is 130℃, and the imprinting pressure is 5MPa.

[0034] The remaining steps and parameters are the same as in Example 1. Example 3

[0035] The difference from Example 1 is as follows: in step three, there are 8 parts of PTFE micro powder (average particle size 3μm) and 8 parts of silicon carbide micro powder (average particle size 10μm); in step four, the plasma treatment power is 400W and the treatment time is 90 seconds; in step five, the hot pressing composite temperature is 170℃, the pressure is 8MPa, and the time is 8 minutes; in step six, the height of the micro-protrusions is 200μm and the surface density is 200 pieces / mm².

[0036] The remaining steps and parameters are the same as in Example 1.

[0037] Comparative Example 1 The difference from Example 1 is that the plasma activation treatment in step four is not performed, and the friction functional layer and the gradient foamed substrate layer are directly hot-pressed together; the resulting product has an interlayer peel strength of only 2.8 N / cm, and delamination occurs after 500 bends.

[0038] Comparative Example 2 The difference from Example 1 is that no nano-silica and silicon carbide micro powder are added to the friction functional layer, and only TPU and SEBS are blended; the resulting product has a dry static friction coefficient of 0.82 and a wet static friction coefficient of 0.51.

[0039] Comparative Example 3 The difference from Example 1 is that the gradient foamed substrate layer is foamed with uniform density (density 0.40 g / cm³) without density gradient; the resulting product has a compression permanent deformation rate of 18% under a load of 300 kg / m² (6% in Example 1), and its anti-slip performance decreases significantly after long-term use.

[0040] Sample grouping: Performance test results: Anti-slip performance (dry / wet friction coefficient): Example 1 showed the best performance, with a dry static friction coefficient of 1.35 and a wet static friction coefficient of 0.95, exhibiting the smallest difference between dry and wet performance. This demonstrates the synergistic effect of the drainage effect of the biomimetic micro-protrusion array and the micro-protrusion effect of nano-silica. Comparative Example 2 (without filler) showed a dry static friction coefficient of only 0.82 and a wet static friction coefficient of only 0.51, representing a decrease of 39.3% and 46.3% respectively compared to Example 1. This fully demonstrates the key contribution of nano-silica and silicon carbide micropowder to the friction coefficient.

[0041] Interlayer bond strength: Example 1 showed an interlayer peel strength of 8.5 N / cm, while Examples 2 and 3 and Comparative Examples 2 and 3 all showed a strength between 7.9 and 8.3 N / cm. Comparative Example 1 (without plasma treatment) showed a strength of only 2.8 N / cm, a decrease of 67.1% compared to Example 1, and delamination occurred after 500 bends, verifying the irreplaceable role of plasma activation treatment in forming interfacial interpenetrating network structures.

[0042] Abrasion resistance and durability: Example 1 showed the highest wear resistance retention rate (92.0%), with excellent friction coefficient retention after 10,000 wear resistance tests; Comparative Example 2 (without filler) had a retention rate of only 75.0%, indicating that inorganic rigid particles play a key role in resisting wear and preventing the friction layer from being worn away.

[0043] Compression and rebound performance: Example 1 showed a compression set of only 6.0%, while Examples 2 and 3, as well as Comparative Examples 1 and 2, all showed a compression set between 6.0% and 7.2%. Comparative Example 3 (uniform density foaming) showed a compression set as high as 18.0%, which is three times that of Example 1. This indicates that the gradient foaming structure can effectively disperse stress, prevent the substrate from collapsing, and ensure anti-slip stability after long-term use.

[0044] Summary of technical advantages: It is understood that the above embodiments are merely exemplary implementations used to illustrate the principles of the present invention, and the present invention is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A manufacturing process for a high-friction, anti-slip composite floor mat substrate, characterized in that, Includes the following steps: Step 1: Preparation of modified SEBS anti-slip masterbatch - By weight, 100 parts of SEBS resin, 30-50 parts of naphthenic oil, 8-15 parts of nano silica, 2-5 parts of silane coupling agent, and 0.5-1.5 parts of antioxidant are added into a high-speed mixer and mixed at 80-120℃ for 15-30 minutes. The mixture is then melt-extruded and granulated using a twin-screw extruder to obtain the modified SEBS anti-slip masterbatch. Step 2: Preparation of Gradient Foamed Substrate Layer – Mix 80-100 parts of EVA resin, 20-40 parts of the modified SEBS anti-slip masterbatch, 3-8 parts of foaming agent, 0.5-2 parts of crosslinking agent, 2-5 parts of zinc oxide, and 0.5-1.5 parts of stearic acid evenly. Then, mix the mixture in an internal mixer at 100-130℃ for 8-15 minutes, and then pass it through a two-roll mill 3-5 times. After sheeting, send it to a flat vulcanizing machine and foam and crosslink at 160-190℃ and 8-15MPa for 8-20 minutes to obtain a gradient foamed substrate layer. The gradient foamed substrate layer has a foam density gradient along the thickness direction, with a foam density of 0.25-0.35 g / cm³ near the upper surface and a foam density of 0.45-0.60 g / cm³ near the lower surface. Step 3: Preparation of the friction functional layer—80-100 parts of thermoplastic polyurethane resin, 30-50 parts of the modified SEBS anti-slip masterbatch, 5-15 parts of polytetrafluoroethylene micro powder, 3-10 parts of silicon carbide micro powder, and 1-3 parts of dispersant are mixed, melt-blended and extruded into granules using a twin-screw extruder, and then cast into a film at 180-220℃ using a casting machine, with a film thickness of 0.2-0.8 mm, to obtain the friction functional layer; Step 4: Plasma activation treatment—The upper surface of the gradient foamed substrate layer and the lower surface of the friction functional layer are subjected to low-temperature plasma treatment. The treatment gas is a mixture of argon and oxygen, the treatment power is 200-500W, and the treatment time is 30-120 seconds. Step 5: Hot-press lamination - The gradient foamed substrate layer after plasma activation treatment is stacked with the triboelectric functional layer. The layer is hot-pressed for 3-10 minutes at a temperature of 150-200℃ and a pressure of 3-10MPa to form an interpenetrating network structure between the triboelectric functional layer and the gradient foamed substrate layer. Step Six: Surface Microstructure Imprinting – On the surface of the friction functional layer of the substrate after hot pressing and lamination, an imprinting roller with a micro-protrusion array is used to perform hot pressing to form a biomimetic micro-protrusion array structure on the surface of the friction functional layer. Step 7: Gradient cooling and shaping – The imprinted composite floor mat substrate is sequentially cooled through three temperature zones. The first temperature zone is 80-100℃, the second temperature zone is 40-60℃, and the third temperature zone is 15-25℃. The dwell time in each temperature zone is 2-5 minutes, resulting in the finished high-friction anti-slip composite floor mat substrate.

2. The production process of a high-friction anti-slip composite floor mat substrate as described in claim 1, characterized in that, The SEBS resin mentioned in step one is a mixture of linear SEBS and star-shaped SEBS, with a weight ratio of linear SEBS to star-shaped SEBS of 1:1 to 3:

1.

3. The production process of a high-friction anti-slip composite floor mat substrate as described in claim 1, characterized in that, The average particle size of the nano-silica in step one is 20-80 nm, and the nano-silica is subjected to segmented coupling treatment. Pre-coating stage: Silane coupling agent accounting for 40%-60% of the total weight of silane coupling agent is mixed with nano silica at a weight ratio of 10:1-5:1 and stirred at 100-120℃ for 1-3 hours to obtain pre-coated nano silica with surface grafted coupling agent and remaining active hydroxyl groups. Secondary bonding stage: The remaining 40%–60% of the silane coupling agent is added together with SEBS resin, naphthenic oil and the above-mentioned pre-coated nano silica in the high-speed mixer described in step one. Under the high temperature and high shear environment of melt blending in a twin-screw extruder, the remaining coupling agent reacts chemically with the remaining hydroxyl groups on the surface of nano silica and the polar groups generated on the SEBS molecular chain due to thermo-oxidation, forming a three-dimensional chemical bonding network of "nano silica—coupling agent—SEBS".

4. The production process of a high-friction anti-slip composite floor mat substrate as described in claim 1, characterized in that, The silane coupling agent mentioned in step one is γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane.

5. The production process of a high-friction anti-slip composite floor mat substrate as described in claim 1, characterized in that, The density gradient change rate of the gradient foamed substrate layer in step two is 0.015−0.035g / cm3 / mm. This density gradient change rate is achieved by adjusting the temperature difference between the upper and lower heating plates of the flat vulcanizing machine. The temperature difference between the upper and lower heating plates is 5−15℃. When the thickness of the substrate decreases, the density difference caused by excessive heat transfer in the thin plate is suppressed by reducing the temperature difference between the upper and lower heating plates or simultaneously reducing the absolute temperature of the upper heating plate.

6. The production process of a high-friction anti-slip composite floor mat substrate as described in claim 1, characterized in that, The average particle size of the silicon carbide micro powder in step three is 5-30 μm, and the average particle size of the polytetrafluoroethylene micro powder is 1-10 μm.

7. The production process of a high-friction anti-slip composite floor mat substrate as described in claim 1, characterized in that, In step four, the volume ratio of the argon and oxygen mixture is 3:1-5:1, and the processing pressure is 20-80 Pa.

8. The production process of a high-friction anti-slip composite floor mat substrate as described in claim 1, characterized in that, The thickness of the interpenetrating network structure described in step five is 50-200 μm.

9. The production process of a high-friction anti-slip composite floor mat substrate as described in claim 1, characterized in that, In step six, the height of the micro-protrusions in the biomimetic micro-protrusion array structure is 50-300μm, the diameter is 30-80μm, the surface density is 100-500 protrusions / mm², and the top of the micro-protrusions is mushroom-shaped or dome-shaped.

10. The production process of a high-friction anti-slip composite floor mat substrate as described in claim 1, characterized in that, The hot pressing composite described in step five is carried out under vacuum conditions, with a vacuum degree of 0.01-0.1 MPa.